Effects of gravity, microgravity or microgravity simulation on early mouse embryogenesis: A review of the first two space embryo studies - Douglas M. Ruden; Daniel A. Rappolee (Mechanobiology in Medicine)
Many simulated micro-gravity (micro-G) experiments on earth suggest that micro-G conditions are not compatible with early mammalian embryo development. Recently, the first two “space embryo” studies have been published showing that early mouse embryo development can occur in real microgravity (real micro-G) conditions in orbit. In the first of these studies, published in 2020, Lei and collaborators developed automated mini-incubator (AMI) devices for mouse embryos facilitating cultivation, microscopic observation, and fixation1. Within these AMI apparatuses, 3400 non-frozen 2-cell embryos were launched in a recoverable satellite, experiencing sustained microgravity (∼0.001G) for 64 ​h post-orbit before fixation in space and recovery on earth. In a subsequent study, in 2023, Wakayama and colleagues2 devised Embryo Thawing and Culturing (ETC) devices, enabling manual thawing, cultivation, and fixation of frozen 2-cell mouse embryos by a trained astronaut aboard the International Space Station (ISS). Within the ETCs, a total of 720 2-cell mouse embryos underwent thawing and cultivation for 4 days on the ISS, subject to either microgravity (n ​= ​360) and simulated-1G (n ​= ​360) conditions. The primary findings from both space embryo experiments indicate that mouse embryos can progress through embryogenesis from the 2-cell stage to the blastocyst stage under real micro-G conditions with few defects. Collectively, these studies propose the potential for mammalian reproduction under real micro-G conditions, challenging earlier simulated micro-G research suggesting otherwise.